2021
DOI: 10.9734/arjom/2021/v17i230272
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Level of the Tenth-grade Students’ Self-Efficacy in Mathematics and its Impact on their Performance: A Study in Pemagatshel District

Abstract: The study aimed at finding out the level of Mathematics self-efficacy and its relationship with the Mathematics performance of tenth-grade students. The study used a quantitative method.  The data was collected from one middle secondary school and three central schools under the Pemagatshel district from 3rd March to 16th March 2020.  A total of 300 students comprising 150 males and females each were included for the study. The data was collected using Mathematics Self-Efficacy Scales and analyzed using SPSS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For example, in a study in the Philippines among secondary school students, the mean mathematics self-efficacy of the students was reported to be moderately high with a mean score of 3.25 (Laranang and Bondoc, 2020). Similarly, in a study of 10th graders in Bhutan, the students' MSE score is reported to be average with a score of 3.25 (Norbu and Dukpa, 2021). Likewise, Perez (2013), who conducted a study in Bangkok, Thailand revealed that more than half of the students showed a self-efficacy score higher than the mean score.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in a study in the Philippines among secondary school students, the mean mathematics self-efficacy of the students was reported to be moderately high with a mean score of 3.25 (Laranang and Bondoc, 2020). Similarly, in a study of 10th graders in Bhutan, the students' MSE score is reported to be average with a score of 3.25 (Norbu and Dukpa, 2021). Likewise, Perez (2013), who conducted a study in Bangkok, Thailand revealed that more than half of the students showed a self-efficacy score higher than the mean score.…”
Section: Discussionmentioning
confidence: 98%
“…The replies for the items are based on a five-point Likert scale where 1 = Strongly Disagree, 2 = Disagree, 3 = Undecided, 4 = Agree, and 5 = Strongly Agree. During analysis, 13 items (Pajares and Miller, 1994;Pajares and Kranzler, 1995a;Wubalem, 2006;Zarch and Kadivar, 2006;Lent et al, 2008;Clutts, 2010;Zedan and Bitar, 2014;Ministry of Education, 2015;Wu, 2016;Cheema, 2018;Probst, 2019;Norbu and Dukpa, 2021) were reverse coded. The highest score, then, represents high mathematics self-efficacy.…”
Section: Instrumentmentioning
confidence: 99%
“…For example, in a study in the Philippines among secondary school students, the mean mathematics self-efficacy of the students was reported to be moderately high with a mean score of 3.25 (Laranang and Bondoc, 2020). Similarly, in a study of 10th graders in Bhutan, the students' MSE score is reported to be average with a score of 3.25 (Norbu and Dukpa, 2021). Likewise, Perez (2013), who conducted a study in Bangkok, Thailand revealed that more than half of the students showed a self-efficacy score higher than the mean score.…”
Section: Discussionmentioning
confidence: 98%
“…Mathematics self-efficacy significantly predicted mathematics achievement in 7th graders in Turkey (Recber et al, 2018). Mathematics self-efficacy significantly predicted mathematics achievement in 10th graders in Bhutan (Norbu and Dukpa, 2021).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation